AN ANALYSIS OF SLANG LANGUAGE STYLES USED IN CHARLIE’S ANGELS MOVIE - Renita Krisdayanti Situmorang; Herman Herman (Journal of English Educational Study (JEES), 2021)
This study was focused on determine the types of use slang language style. The types of slangs were analyzed from “Charlie’s Angels” movie. Theories used in this research were Sumarsono (2007) about the types of slang language style and Zhou & Fan (2013) about the functions of slang language. This study was conducted using a descriptive qualitative method.This research is the kind of content analysis study based on the way to do qualitative research. The way to collects the data are; downloading movie, watching movie and downloading movie subtitle. The data were from a movie entitled “Charlie’s Angels” in the year of 2019 with action-comedy genre.After conducting the analysis, this study showed that there were four types of slang language style from six types of slang language. They were clipping, creative, uses the existing words and metaphor. Creative was found as the most dominant types of slang language style in the movie with 10 data (40%), metaphor with 7 data (28%), uses the existing words with 5 data (20%) and clipping with 3 data (12%). Finally, the reseacher hopes that this study will be useful for the future improvement of studying literature, especially about slang language style